Cone-Beam Computed Tomography Assessment of Root Canal Transportation by Neoniti and Reciproc Single-File Systems - Moazzami, Fariborz; Khojastepour, Leila; Nabavizadeh, Mohammadreza; Seied Habashi, Mina (Iranian Endodontic Journal, 2016)
Introduction: The aim of this in vitro study was to compare the canal transportation of two single-file engine-driven systems, Neoniti and Reciproc, using cone-beam computed tomography (CBCT). Methods and Materials: Forty-five non-calcified roots with mature apices and apical curvature of 15-30 degrees were selected from extracted human maxillary molars for this study. Samples were randomly divided into two groups (n=20) and a control group (n=5) and canal preparation with either system was performed according to manufacturers' instructions. Pre- and post-instrumentation CBCT images were captured and the amount of canal transportation within the files was calculated at levels of 3, 4, and 5 mm from the apex. The independent sample t-test was used to analyze the statistical significance between the two groups. The level of significance was defined at 0.05. Results: Reciproc created more canal transportation compared to Neoniti in both mesiodistal and buccolingual directions. The difference between the two systems was statistically significant in all evaluated distances from the apex (P<0.001). During this study fracture of one file (25/0.08) in the Neoniti group occurred. Conclusion: Neoniti and Reciproc systems have significant difference in terms of creating canal transportation. Reciproc created more canal transportation in buccolingual and mesiodistal dimensions. Keywords: Canal Transportation; Cone-Beam Computed Tomography; Neoniti; Reciproc; Root Canal Preparation